State of the antioxidant system in mitochondria of skin cells during experimental B16/F10 melanoma growth with chronic neurogenic pain - E. M. Frantsiyants; I. V. Neskubina; E. I. Surikova; L. K. Trepitaki; L. A. Nemashkalova; I. V. Kaplieva; N. S. Lesovaya (Бюллетень сибирской медицины, 2020)
Aim. To study the state of the antioxidant system in mitochondria of skin cells during B16/F10 melanoma growth in mice with chronic neurogenic pain.Materials and methods. The study included female С57ВL/6 mice (n = 28). Experimental groups included an intact group, a control group – chronic neurogenic pain model, a comparison group – standard subcutaneous transplantation of В16/F10 melanoma, and a main group – transplantation of  В16/F10 melanoma 3 weeks after creation of a model of chronic neurogenic pain. Animals were decapitated on day 14 of the В16/F10 melanoma growth, the skin was excised and mitochondria were isolated. Standard ELISA test systems were used to determine the levels of reduced glutathione (GSH) and oxidized glutathione (GSSG) (Bio Source, USA); glutathione peroxidase-4 (GPx 4) (Clod-Clon Corporation, CNDR); glutathione reductase (GR) (Cusabio, CNDR); glutathione S-transferase (G-S-T) (Ivvundiagnostik, Germany); glutathione peroxidase-1 (GPx 1), and superoxide dismutase-2 (SOD-2) (Ab Frontier, South Korea).Results. Mitochondria of skin cells in controls showed an increase in the levels of GSH by 1.3 times, GPx 1 – by 2.9 times, GPx 4 – by 1.9 times, GR – by 2.8 times, and SOD-2 – by 2.4 times, compared to intact animals. Changes in the comparison group were opposite: GPx 1 decreased by 1.9 times, GPx 4 – by 3.7 times, GR – by 3.9 times, SOD-2 – by 3.8 times, and GSSG rose by 1.36 times compared to intact animals. The growth of melanoma with chronic neurogenic pain caused an increase in the levels of GSH by 1.5 times, GPx 1 – by 3.6 times, G-S-T – by 1.28 times, GPx 4 – by 1.6 times, and SOD-2 – by 1.8 times, compared to intact animals.Conclusions. The growth of В16/F10 melanoma together with chronic neurogenic pain restructures the antioxidant system of skin mitochondria towards generation of reductive stress under the influence of chronic pain, which can affect the growth and development of experimental melanoma.